Development of The Profile Pancasila Students in Early Childhood Dimensions - Eko Suhendro (Universitas Muhammadiyah Ponorogo, 2022)
The philosophy of life about Pancasila that the founders of the nation formulated has become the leading centre carried out by the Ministry of Research, Technology and Culture in forming the Pancasila profile. It is hoped that future generations can help Indonesian children grow into an age that is smart and characterful and can face the career world and the upcoming era of globalization. This study aims to analyze the development of Pancasila student profiles in the early childhood dimension. The method used in this study is qualitative with descriptive analysis techniques with library review (Library Research). Data collection was sourced from teachers in Indonesia, scientific journals, proceedings, books, associations, and scientific forums. The results of the literature review found that the development of a profile of Pancasila students in early childhood is very important in order to prepare for their future to become an intelligent generation with character. The new findings of this study are that development can be carried out by implementing 6 Pancasila student profiles and developed according to each profile adjusted to the dimensions of early childhood, while the implementation of learning to characterize the Pancasila student profile can be carried out by implementing project-based learning carried out in a series of learning processes.